Implementasi Metode Time Blocking dalam Meningkatkan Motivasi Kerja - Syamsu Rizal, Anis; Sirajuddin; Sevty Wahiddirani Saputri (Universitas Pamulang, 2026)
Taman Bacaan Perigi is a social institution focused on improving literacy and community empowerment, not only as a reading center but also as a vehicle for developing the capacity of local workers such as artisans, small traders, teachers, and volunteers. Observations indicate that many of the workers under their care experience difficulty managing time, setting priorities, and balancing work demands with personal needs. This condition leads to work delays, suboptimal work results, and decreased motivation. To address these issues, the Time Blocking method is offered as an effective time management strategy. The implementation of this method will be carried out at Taman Bacaan Perigi, Sawangan District, Depok City, which has a community of workers under their care from various sectors. The target group is 20–30 workers aged 20–45 who are active in the institution's activities. The application of time blocking is relevant for workers who carry out multiple roles simultaneously. It is hoped that it will help them create realistic schedules, reduce stress, and increase enthusiasm in carrying out their daily routines. Keywords: Time Blocking, Work Motivation